Critique and Reflexivity: Exploring the “C” in C/ritical Discourse Studies (CDS) Introduction: The Editors’ View - Stamou, Anastasia G.; Gounari, Panayota; Boukala, Salomi (The Greek Review of Social Research, 2025)
Critical Discourse Studies (CDS) stands apart from “non-critical” approaches by not only analyzing the role of language in society, but by examining how and why it is entangled with power relations and ideology. Yet, what constitutes the “critical” in CDS often remains conceptually ambiguous. This Special Issue addresses these ambiguities, focusing on ideology, power, critique, and reflexivity. Bringing together contributions primarily from Greek scholars, it aims to foster reflexive, intertextual dialogue and to advance the academic recognition and institutional presence of CDS in Greece, while also engaging broader questions about its evolving meaning and role in critical scholarship.